1990
DOI: 10.1080/10601329008544807
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-Liquid Equilibrium of Copolymer Solutions with Broad and Asymmetric Chemical Distributions

Abstract: A solution of a random copolymer showing polydispersity only with respect to chemical composition is considered. A model distribution very flexible in its breadth and in its asymmetry is used to describe the polydispersity. Based on continuous thermodynamics, equations for the cloud-point curve, the shadow curve, the spinodal, the critical point, and the heterogeneous double critical point are derived. The activity coefficients are calculated with the aid of Huggins' x-parameter concept assuming x to depend li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…On the basis of theoretical considerations in the framework of the Flory−Huggins theory, Scott demonstrated that copolymers of high molecular weight must be reasonably uniform in composition to warrant the stability of a homogeneous phase . Ratzsch and co-workers have studied the effect of compositional polydispersity on the phase behavior of random copolymer solutions using continuous thermodynamics. They found that the compositional polydispersity of the copolymers had an effect on the phase behavior of the copolymer solutions, but they were not able to quantify that effect because the theoretical model used for their calculations had not been used to describe the phase behavior of real systems. In this work, we will take advantage of a recently developed modeling concept for branched polyolefins in the framework of the PC-SAFT equation of state to quantify the effect of SCDB on the phase behavior of LLDPE solutions.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of theoretical considerations in the framework of the Flory−Huggins theory, Scott demonstrated that copolymers of high molecular weight must be reasonably uniform in composition to warrant the stability of a homogeneous phase . Ratzsch and co-workers have studied the effect of compositional polydispersity on the phase behavior of random copolymer solutions using continuous thermodynamics. They found that the compositional polydispersity of the copolymers had an effect on the phase behavior of the copolymer solutions, but they were not able to quantify that effect because the theoretical model used for their calculations had not been used to describe the phase behavior of real systems. In this work, we will take advantage of a recently developed modeling concept for branched polyolefins in the framework of the PC-SAFT equation of state to quantify the effect of SCDB on the phase behavior of LLDPE solutions.…”
Section: Introductionmentioning
confidence: 99%